Precision medicine and personalized approach in vitiligo. Issue 5 (15th September 2022) - Ahuja, Rhea; Narayanan, B.; Gupta, Somesh
Abstract: Precision medicine involves stratification of patients based on clinical, lifestyle, genetic, and biomarker information to decide further treatment and prognosticate, moving beyond classical "signs‐and‐symptoms" approach. This evolving concept is gaining ground in the management of various dermatological diseases like psoriasis, atopic dermatitis, urticaria and pemphigus; however it is relatively in its infancy with respect to its application in vitiligo. This review aims to highlight the role of precision medicine in vitiligo, with a focus on genetic makeup, immunological factors, clinical subtypes, disease biomarkers, and dermoscopic signs in predicting therapeutic response to medical or surgical modalities, including light therapy.